Fibroblast growth factor receptor 3 interacts with and activates TGFβ-activated kinase 1 tyrosine phosphorylation and NFκB signaling in multiple myeloma and bladder cancer - Salazar, Lisa; Kashiwada, Tamara; Krejci, Pavel; Meyer, April N; Casale, Malcolm; Hallowell, Matthew; Wilcox, William R; Donoghue, Daniel J; Thompson, Leslie Michels (PloS one, 2014)
Cancer is a major public health problem worldwide. In the United States alone, 1 in 4 deaths is due to cancer and for 2013 a total of 1,660,290 new cancer cases and 580,350 cancer-related deaths are projected. Comprehensive profiling of multiple cancer genomes has revealed a highly complex genetic landscape in which a large number of altered genes, varying from tumor to tumor, impact core biological pathways and processes. This has implications for therapeutic targeting of signaling networks in the development of treatments for specific cancers. The NFκB transcription factor is constitutively active in a number of hematologic and solid tumors, and many signaling pathways implicated in cancer are likely connected to NFκB activation. A critical mediator of NFκB activity is TGFβ-activated kinase 1 (TAK1). Here, we identify TAK1 as a novel interacting protein and target of fibroblast growth factor receptor 3 (FGFR3) tyrosine kinase activity. We further demonstrate that activating mutations in FGFR3 associated with both multiple myeloma and bladder cancer can modulate expression of genes that regulate NFκB signaling, and promote both NFκB transcriptional activity and cell adhesion in a manner dependent on TAK1 expression in both cancer cell types. Our findings suggest TAK1 as a potential therapeutic target for FGFR3-associated cancers, and other malignancies in which TAK1 contributes to constitutive NFκB activation.
Keywords: Oligonucleotide Array Sequence Analysis; fosforylace; Peptide Fragments; techniky dvojhybridového systému; Phosphorylation; MAP Kinase Kinase Kinases; Two-Hybrid System Techniques; Tumor Cells, Cultured; Cell Proliferation; Immunoprecipitation; buněčná adheze; nádorové biomarkery; stanovení celkové genové exprese; Humans; mnohočetný myelom; Biomarkers, Tumor; Receptor, Fibroblast Growth Factor, Type 3; Multiple Myeloma; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Transforming Growth Factor beta; proliferace buněk; MAP kinasy kinas (kinas); Urinary Bladder Neoplasms; sekvenční analýza hybridizací s uspořádaným souborem oligonukleotidů; Cell Adhesion; RNA, Messenger; spektrometrie hmotnostní - ionizace laserem za účasti matrice; Reverse Transcriptase Polymerase Chain Reaction; tyrosin; nádorové buňky kultivované; nádory močového měchýře; apoptóza; western blotting; receptor fibroblastových růstových faktorů, typ 3; transformující růstový faktor beta; Gene Expression Profiling; peptidové fragmenty; Blotting, Western; Real-Time Polymerase Chain Reaction; kvantitativní polymerázová řetězová reakce; lidé; polymerázová řetězová reakce s reverzní transkripcí; Signal Transduction; Tyrosine; imunoprecipitace; NF-kappa B; Apoptosis; signální transdukce; messenger RNA